AI-Augmented Model-Based Systems Engineering - Bernijazov, Ruslan; Dumitrescu, Roman; Hanke, Fabian; von Heißen, Oliver; Kaiser, Lydia; Tissen, Denis (Zeitschrift für wirtschaftlichen Fabrikbetrieb)
Abstract The increasing complexity of modern technical systems necessitates innovative approaches such as Model-Based Systems Engineering (MBSE). In this context, using Artificial Intelligence (AI) emerges as a key enabler for practical application and efficiency improvement. This article introduces a maturity model for AI-based assistance systems in MBSE. It helps companies assess their current automation level in MBSE activities, providing a foundation for strategic planning of process improvements.

Chances of smart Views: Integration of Stakeholder perspectives using videobased Views in MBSE - Förster, Felix; Bausen, Steffen; Bernijazov, Ruslan; Koldewey, Christian; Dumitrescu, Roman; Bursac, Nikola (Stuttgarter Symposium für Produktentwicklung SSP 2025)

Using SysML as a Modelling Language for Dataspaces - Kulkarni, Pranav Jayant; Zerbin, Julian; Koldewey, Christian; Bernijazov, Ruslan; Dumitrescu, Roman (2024 IEEE International Conference on Technology Management, Operations and Decisions (ICTMOD))
Utilizing data is crucial for economic success, but a lack of interoperability and concerns about the misuse of ones own data are hindering the cross-organizational use of data. Dataspaces provide the infrastructure necessary to integrate heterogeneous data sources within an organization or ecosystem, enabling seamless data interaction and interoperability. In addition, data spaces strengthen data sovereignty through their decentralized nature, which enables organizations to effectively control and manage their data. However, challenges persist in managing the complexity and dynamic nature of dataspaces, requiring significant resources and technical expertise. The decentralized nature leads to a large and diverse number of stakeholders, who need to agree on the use and scope of a dataspace. Modeling is a common approach to cope with technical complexity and heterogeneous stakeholders. In this paper, we propose a version of SysML and a corresponding method that focus on the modelling of data spaces. We provide a dataspace modelling method to unify the understanding of dataspaces and scope among all stakeholders to simplify the design and development process.
Keywords: Dataspaces; Modelling; SysML; Gaia-X; System Specification

Towards Automated Design: Automatically Generating Modeling Elements with Prompt Engineering and Generative Artificial Intelligence - Kulkarni, Pranav Jayant; Tissen, Denis; Bernijazov, Ruslan; Dumitrescu, Roman (DS 130: Proceedings of NordDesign 2024)
Developing Intelligent Technical Systems (ITS) involves a complex process encompassing planning, analysis, design, production, and maintenance. Model-Based Systems Engineering (MBSE) is a key methodology for systematic systems engineering. Designing models for ITS requires harmonious interaction of various elements, posing a challenge in MBSE. Leveraging Generative Artificial Intelligence, we generated a dataset for modeling, using prompt engineering on large language models. The generated artifacts can aid engineers in MBSE design or serve as synthetic training data for AI assistants.
Keywords: Data Driven Design; Design Automation; Systems Engineering (SE); Artificial Intelligence (AI)

Spearhead Data-Driven Model-Based Systems Engineering: Interview Study on Definition, Preconditions, Challenges, Potentials, and Use Cases - Tissen, Denis; Wiederkehr, Ingrid; Bernijazov, Ruslan; Koldewey, Christian; Dumitrescu, Roman (DS 130: Proceedings of NordDesign 2024, Reykjavik, Iceland, 12th - 14th August 2024)

A Maturity Model for Data-Driven Model-Based Systems Engineering for Producing Companies - Tissen, Denis; Bernijazov, Ruslan; Koldewey, Christian; Dumitrescu, Roman (DS 134: Proceedings of the 26th International DSM Conference (DSM 2024), Stuttgart, Germany)

A Maturity Model for Data-Driven Model-Based Systems Engineering for Producing Companies - Tissen, Denis; Bernijazov, Ruslan; Koldewey, Christian; Dumitrescu, Roman (Proceedings of the 26th International DSM Conference (DSM 2024), Stuttgart, Germany)

Portals across domains: A data analysis task and documentation canvas for data-driven model-based systems engineering - Tissen, Denis; Wiederkehr, Ingrid; Bernijazov, Ruslan; Koldewey, Christian; Dumitrescu, Roman

Towards Automated Design: Automatically Generating Modeling Elements with Prompt Engineering and Generative Artificial Intelligence - Kulkarni, Pranav Jayant; Tissen, Denis; Bernijazov, Ruslan; Dumitrescu, Roman (Proceedings of NordDesign 2024)

Portals across domains: A data analysis task and documentation canvas for data-driven model-based systems engineering - Tissen, Denis; Wiederkehr, Ingrid; Bernijazov, Ruslan; Koldewey, Christian; Dumitrescu, Roman (System Innovation for an Artificial Intelligence Era)